HIV‐associated dysbiosis and immune recovery during antiretroviral therapy - Samuel D. Johnson; Siddappa N. Byrareddy (Wiley, 2022)
Abstract The microbiomes of people living with HIV (PLWH) are significantly dysregulated with a loss of bacteria diversity and shifts in composition, including increases in pathogenic and decreases in beneficial species. Because of the microbiome's role in modulating health, the effect of this dysbiosis on immune response in PLWH has been a significant concern, mainly because these shifts can persist even after viral suppression during combination antiretroviral therapy (cART). However, due to limitations on sample availability, few studies have been able to provide insights into these microbiome‐immune interactions. Recently, Olivas‐Martínez et al. characterized ileum and caecum mucosa‐associated microbiomes of PLWH based on their level of peripheral CD4+ T‐cell reconstitution following long‐term cART. Their analysis revealed distinct microbiome signatures predictive of recovery. Additionally, differences in markers of gut inflammation and damage between response groups were described, further implicating mucosal disruptions with immune reconstitution. These new data demonstrate an interdependence of microbiome and therapy response, and additional studies are urgently required to fully elucidate this crosstalk and microbiome dynamics from before/after infection and finally, long‐term viral suppression with cART.